2016
DOI: 10.1016/j.niox.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase induces heat shock protein HSPA6 (HSP70B′) in human arterial smooth muscle cells

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…NO is an important neurotransmitter secreted by vascular endothelial cells and has numerous functions, including inhibiting monocyte-macrophage and platelet adhesion, decreasing the monolayer permeability of vascular endothelial cells and reducing vascular endothelial cell and smooth muscle cell proliferation (33). A total of 30% NO in the blood is derived from endothelial nitric oxide synthase genes expressed by vascular endothelial cells (34). The present study detected NO level and NOS activity under high glucose conditions.…”
Section: Discussionmentioning
confidence: 50%
“…NO is an important neurotransmitter secreted by vascular endothelial cells and has numerous functions, including inhibiting monocyte-macrophage and platelet adhesion, decreasing the monolayer permeability of vascular endothelial cells and reducing vascular endothelial cell and smooth muscle cell proliferation (33). A total of 30% NO in the blood is derived from endothelial nitric oxide synthase genes expressed by vascular endothelial cells (34). The present study detected NO level and NOS activity under high glucose conditions.…”
Section: Discussionmentioning
confidence: 50%
“…G894T polymorphism results in reduced eNOS enzymatic activity and decreased production of NO by endothelial cells [ 30 ]. Reduced eNOS activity causes an increase in smooth muscle cell proliferation after vascular injury, and inhibition of the endothelial NO pathway are present in atherosclerosis [ 31 32 ]. Zhang et al reported eNOS G894T polymorphism may play an important role in CAD development among Asia population [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, a cluster of heat shock protein member A (HSP70) gene family members including HSPA1A (also named HSP70A), HSPA1B (also named HSP70B), HSPA5 and HSPA8 was amongst the genes up-regulated, which were associated with endothelial function (Fig. 5E ) 27 , 28 . Moreover, we identified growth arrest and DNA-damage-inducible protein (GADD45) genes including GADD45A, GADD45B and GADD45G were also significantly up-regulated, which have been implicated in stress signaling to activate several stress response kinase such as P38 MAPK, thus resulting in apoptosis (Fig.…”
Section: Resultsmentioning
confidence: 99%